Kostum Dalam Membangun Karakter Tokoh Pada Film Soekarno - Sintowoko, Dyah Ayu Wiwid; Sugihartono, Ranang Agung (Capture : Jurnal Seni Media Rekam, 2014)
This study discusses the procedures of costumes and characters in the Sukarnofilm. This qualitative descriptive research apply the Sukarno film as source of data. Thecollection of data by purposive sampling, with the method of observation, interviews,and literature. Data were analyzed through data reduction, data display, drawingconclusions and verification process. The results showed that the costumes portraythe characterization of the characters. Costume adjusted with basic clothing, headclothing, body clothing, legs underwear, and accessories are known for costume parts.Each character has a unique costume and a differentiator from other figures. Costumealso build characterization of actors according to the physiological dimension (neatness,cleanliness, beauty, beauty, valor, charm, charisma, and authority). Sociological dimensionsindicate socioeconomic class, role in the family / community, ideology, ancestry, levelof education, religion, ethnicity / race, and interaction between the actors. While thepsychological dimensions adapted to the atmosphere and scene. Color and layoutcostume describing feelings, honesty, sincerity, emotion, desire, desire, passion, inneraction, as well as the vision of each character in the film.Keywords: costume, characterization, actor, film, and Soekarno